Respon Islam terhadap Perkembangan Ilmu Pengetahuan pada Kasus Operasi Plastik - Mitha Mahdalena Efendi; Muhammad Alwi HS; Fatimah Al-Zahrah (Matan : Journal of Islam and Muslim Society, 2020)
This article discusses the Islamic response, especially qv. An-Nisa / 4: 119 and Al-Bukhari's hadith in the Sahih Al-Bukhari book number Hadith 5943, on plastic surgery as a result of the development of science. This departs from the fact that the development of science influences human lifestyles, one of which is plastic surgery. From here, plastic surgery is one of the modern-contemporary issues that is often done by humans, including Muslims, so it needs attention from religious aspects. This article is a literature study, namely describing as well as analyzing sources related to research, both commentaries, the book of hadith sharia, and other sources. The result of this article is that plastic surgery may be performed if it is needed to treat and repair parts of the human body. Conversely, plastic surgery is forbidden if done only for a moment of pleasure and damage to body parts. From here, there are theological and social aspects in the Islamic proposition for plastic surgery. From the theological aspect, plastic surgery based on momentary pleasure or beauty will be among those who follow the path of Satan so that he is cursed by Allah swt. While from the social aspect, plastic surgery is carried out for the benefit of repairing and treating body parts that are defective, then the act may be carried out.